Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve the system by substitution.
1. y = -6x – 7
y = -7x

2. -y=x
3x+5y=20



Sagot :

YujiC

Answer:

For no. 1:

One of the equations say that y=-7x

So plug in -7x to the other equation as y so you equation would be

-7x= -6x-7

And then, just solve for the variable:

*add -6x to both sides*:

-x= -7

*multiply both by negative one to get a positive variable*

FOR NUMBER 1, THE ANSWER IS:

x=7

Y=-7

For no. 2:

-y=x and your other equation is 3x+5y=20

Plug in x as -y:

-3y+5y=20

*simplify*

2y=20

*divide by 2 on each side to get 1 variable alone*

Y=10

FOR NUMBER 2, THE ANSWER IS:

x=-y

Y=10